Market Behaviour of Young Adults in The Area of Sharing Economy During The COVID-19 Pandemic – On the Example of Virtual Groups - Anna Irena SZYMAŃSKA (Communications of International Proceedings, 2021)
The COVID-19 pandemic contributed to social isolation and crisis in selected sectors of the economy and severely impacted human behaviour in the sharing economy. When analysing the literature, a research gap was identified both in the sharing economy and in the analysis of human behaviour in the SE during the pandemic. The only available publications offer general information on the topic and present sample studies on the development of SE in tourism, transport and urban life. This article broadens knowledge on changes in young adults' behaviour in the SE area during the COVID-19 pandemic. Primarily, the research was targeted at defining the stimulants of the SE development among young consumers during the COVID-19 pandemic. Initially, four research questions had been formulated and subsequently answered on the basis of the research results. In terms of duration, the empirical research stretched from February 2020 to April 2021 and focused on members of the SE Internet group. In the research, a triangulation method was used, involving a desk analysis and observation (both passive and disguised participative observation) and focus group interviews. The subject was further analysed by using qualitative methods. The research showed that the activity in the SE Internet groups, which involved the activities that did not require any direct meetings, was definitely more intensive. Online contacts served improvement of both physical and mental state of their participants. In addition, a surge in entrepreneurial behaviour was also observed in the analysed Internet groups.
Keywords: Disguised Participative Observation; Focus Group Interview; Internet Group; Passive Observation; Sharing Economy; Virtual Group; Qualitative Research; Young Adults.